PENGARUH PRICE PERCEPTION TERHADAP REPURCHASE INTENTIONDIMEDIASI OLEH PERCEIVED VALUE(Studi Pada Pelanggan Luxcrime di E-Commerce) - Indry Olivia Br Barus; I Wayan Santika (BORJUIS: JURNAL OF ECONOMY, 2026)
The purpose of this study is to examine and explain the effect of price perception on repurchase intention by incorporating perceived value as a mediating variable among Luxcrime customers on e-commerce platforms. The population of this study consists of Luxcrime customers residing in Denpasar City who have purchased Luxcrime products through e-commerce platforms. A total of 120 respondents were selected using a purposive sampling technique, and the data were collected through questionnaires. This study employed descriptive and inferential statistical analyses using the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). The results indicate that price perception has a positive and significant effect on repurchase intention, price perception has a positive and significant effect on perceived value, and perceived value has a positive and significant effect on repurchase intention. In addition, perceived value significantly mediates (partial mediation) the relationship between price perception and repurchase intention. The theoretical implication of this study is that it reinforces the Stimulus-Organism-Response (S-O-R) Theory in explaining repurchase intention, while the practical implication highlights the importance of maintaining a positive price perception and enhancing customers' perceived value in order to increase repurchase intention toward Luxcrime products on e-commerce platforms.